Lifestyle Modification Therapy For Optimism And Health-Related Behaviour In COVID-19 Positive Middle-Aged Adults: An Experimental Study (International Journal of Food and Nutritional Sciences, 2022)
The challenging social situation arising due to the coronavirus outbreak leads to so many mental health issues. In this scenario, it was essential to boost the optimism in people because optimism denotes the positive side of mental health. Lifestyle has been known to bring about positive changes in psychological well-being. In this context, the present study was planned to assess the impact of lifestyle modification counselling on the optimism and health-related behaviour of COVID-19 positive middle aged adults. To conduct the study 192 COVID-19-positive subjects from the Raipur District of Chhattisgarh were selected as a sample which includes both males and females. The age range of the sample was 40-60 years. The selected subjects were divided into two groups i.e. experimental and control groups with an equal number of subjects randomly assigned. Lifestyle counselling was given for three months to the subjects of the experimental group. The health-related behaviour of the subjects was assessed with the help of the FANTASTIC Lifestyle Checklist while optimism was assessed through a scale prepared by Ajwani (2002).